SPORTS LEARNING METHODS BASED ON ISLAMIC VALUES - Jani, Egi; Topo Yono; M Saleh Nurhasyim (UNIVERSITAS NEGERI JAKARTA POSTGRADUATE OF PHYSICAL EDUCATION DEPARTMENTS, 2025)
The principles of Islam in sports play a crucial role in shaping students with strong character and integrity. This research is a literature study aimed at analyzing various relevant sources. Several Islamic values that can be applied in the world of sports include faith and devotion to Allah, discipline, hard work and perseverance, social awareness, justice, patience and inner peace, as well as humility. By applying Islamic values in sports, students can develop a healthy and positive character while contributing to the creation of a harmonious and peaceful sports environment. Additionally, Islamic values can help students overcome various challenges and obstacles during the learning process. Therefore, for Muslim students, understanding and practicing Islamic values in sports is highly important. The application of these values not only contributes to the improvement of sports learning but also strengthens personal character and deepens their Islamic faith.